Evaluation of Favorable Shale Gas Intervals in Dawuba Formation of Ziyun Area, South Qian Depression - Kun Yuan; Wenhui Huang; Xinxin Fang; Ting Wang; Tuo Lin; Rong Chen (Geofluids)
A series of qualitative descriptions and quantitative analyses was used to determine the lithofacies characteristics and recognize the favorable shale intervals of Dawuba Formation in the Ziyun area of South Qian Depression. The qualitative descriptions include core description and scanning electron microscope (SEM) observation. The quantitative analyses include X-ray diffraction, total organic content analysis, vitrinite reflectance, maceral composition, porosity, and permeability, as well as gas and element composition. The Dawuba Formation could be divided into four members. In general, the shale in the first and third members showed similarly high organic matter content with most samples in range of 2–2.5% and higher brittle mineral content with a content of quartz 40.53% and 33.21%, respectively, compared with the other two members, as well as high gas content. However, the first member shale samples exhibited much higher porosity and permeability than the third member shale samples. Furthermore, the shale gas in the first member was chiefly composed of methane (average: 83.63%), while that in the third member mainly consisted of nitrogen (average: 79.92%). Hence, the first member should be regarded as the most favorable target.